THE LIFE AND TIMES OF HARIHARA I: FOUNDER OF VIJAYANAGARA - Revanasiddappa S (ShodhKosh: Journal of Visual and Performing Arts, 2024)
Harihara I, also known as Hakka, was the pivotal figure behind the founding of the Vijayanagara Empire in 14th-century South India, a period marked by political fragmentation and external invasions. Emerging amid the decline of the Hoysala kingdom and the aggressive expansion of the Delhi Sultanate into the Deccan, Harihara I, alongside his brother Bukka Raya I, established a powerful and enduring Hindu kingdom around 1336 CE. The foundation of Vijayanagara near the Tungabhadra River represented not only a strategic military move but also a symbolic renaissance of Hindu culture and political authority in the region. Harihara’s reign (circa 1336–1356 CE) was characterized by the consolidation of territories in present-day Karnataka, Andhra Pradesh, and Tamil Nadu, where he reasserted indigenous rule after decades of turmoil. He combined military prowess with religious revivalism, restoring and protecting Hindu temples and religious institutions that had suffered during earlier invasions. A significant innovation of his rule was the establishment of the Nayaka system—a decentralized administrative structure that delegated authority to loyal provincial governors responsible for local governance and defense, ensuring stability over a vast empire. Harihara I’s alliance with the spiritual leader Vidyaranya reinforced the ideological foundation of his rule, projecting Vijayanagara as a dharmic kingdom committed to righteous governance. Beyond military and religious achievements, Harihara encouraged economic growth through agricultural expansion and the promotion of internal and coastal trade networks, fostering prosperity and cultural synthesis. Harihara I’s life and reign symbolize a remarkable era of resilience and renewal in South Indian history. His vision laid the groundwork for the Vijayanagara Empire to flourish as a major political, cultural, and economic power for over two centuries, leaving a lasting legacy celebrated for its architectural marvels, artistic achievements, and inclusive governance.